2017
DOI: 10.1542/peds.2017-2059
|View full text |Cite
|
Sign up to set email alerts
|

Beliefs Regarding Development and Early Intervention Among Low-Income African American and Hispanic Mothers

Abstract: Understanding maternal health beliefs and expectations regarding DD and EI, acknowledging the influence of social networks on help-seeking, and addressing social and financial stressors are critical to ensuring that children with DD are identified and supported at an early age.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 30 publications
2
30
0
Order By: Relevance
“…Families looking for support systems have been a common theme in other populations of children with special health care needs, such as cancer, developmental delay, and autism [49,50]. Parents in our study were seeking communities that have experienced the same journey as they have.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Families looking for support systems have been a common theme in other populations of children with special health care needs, such as cancer, developmental delay, and autism [49,50]. Parents in our study were seeking communities that have experienced the same journey as they have.…”
Section: Discussionmentioning
confidence: 99%
“…Parents in our study were seeking communities that have experienced the same journey as they have. A handful of studies have examined the role of social media websites and forums and their impact on parenting and help-seeking behaviors [49,51]. For example, Thoren et al evaluated the content of communication in 1497 Facebook communities dedicated to preterm infants and found that "information sharing" (31%) and "interpersonal support" (53%) were the most common purposes of use of the Facebook groups [52].…”
Section: Discussionmentioning
confidence: 99%
“…Competing priorities Poor environmental circumstances or hazards can be root causes of physical health problems and can be related to living in poverty, war or hunger, especially in very low-income settings (WHO, 2008b). The priorities of caregivers may be mainly centred around social and financial stressors, resulting in decreased attention to the mental wellbeing and developmental trajectory of a child (Magnusson, Minkovitz, Kuhlthau, Caballero, & Mistry, 2017). As a consequence, atypical behaviour may be overlooked or there may be a delay in the process of recognition.…”
Section: Caregivers' Awareness Of the Mental Health And Developmentalmentioning
confidence: 99%
“…1,15 Known barriers to connection for families include not understanding the referral process, concerns that the child or family will experience stigma if delays are revealed, and logistical barriers to obtaining services. 16,17 Because minimizing long-term disability depends on both appropriate screening as well as connection to effective developmental services, it is essential that developmental screening in primary care be bolstered by systems that facilitate referral completion and follow-up.…”
Section: Quality Reportmentioning
confidence: 99%